Cultural Influences in Deceptive Communication - McLeod, Ann Beverly (My University, 1988)
Researchers in deceptive communication have suggested that beliefs about deceivers (e.g., Hocking & Leathers, 1980; Ramsey, 1979), and the behavioural changes exhibited by deceivers (e.g., Ekman & Friesen, 1972; Feldman, 1979), and the accuracy with which deceptive messages can be detected (Atmfyanandana, 1976; Ekman, 1985) are influenced by cultural factors. To date, there has been no empirical evidence to support these hypotheses.
The purpose of research presented in this thesis was to examine the role of cultural factors in deceptive communication. To this end, Canadian and Chinese students were compared regarding their attitudes towards deception, their beliefs about the behavioural changes exhibited by deceivers, the behavioural changes exhibited during deception, and their judgements of the sincerity of communicators.
The results of this research indicated that, compared to Canadian students, Chinese students rate lying as less morally wrong, and believe people to exhibit significantly fewer behavioural changes when telling lies. Analyses of judges' assessments of the sincerity of Canadian and Chinese communicator revealed that messages by Chinese female communicators were judged more accurately than messages by Chinese male communicators. This gender difference was not apparent in ratings of the messages by Canadian male and female communicators. Differences were also found in Canadian and Chinese students' assessments of the sincerity of the communicators. Chinese judges, rated the sincerity of the communicators as higher than did the Canadian judges, and Chinese judges were less accurate at detecting deceptive messages by Canadian communicators than were the Canadian judges.
Misattributions of insincerity or inappropriate expectations regarding sincerity can promote negative cultural stereotypes and inhibit effective communication between interactants from different culturaI backgrounds. Awareness of differences in attitudes and beliefs about deception, and in assessments of the sincerity of communicators may help to facilitate communication and understanding between Canadian and Chinese individuals.
Keywords: Psychology; Psychology